Genetic analysis of "leucine-rich repeat (LRR) and immunoglobulin (Ig) domain-containing, Nogo receptor-interacting protein-1 (LINGO1)" in two independent Chinese parkinson's disease populations - Wu, Y.-R. (2014)
10.1002/ajmg.b.31124